Literature Review : Analisis Kebijakan Pengelolaan Limbah Medis Padat Rumah Sakit - Sarwendah Sarwendah; Herniwanti Herniwanti (Jurnal Sehat Mandiri, 2026)
The management of hazardous and toxic solid medical waste (B3) in hospitals remains a critical issue due to its potential to cause infection risks and environmental pollution if not properly managed. In Riau Province, the compliance level of health facilities with medical waste management standards is still low, while the volume of waste continues to increase. This study aims to analyze the overview of management practices, identify the types of medical waste, and examine policies related to the management of B3 solid medical waste in hospitals in Riau Province. The study employed a Systematic Literature Review (SLR) method by searching scientific articles through the Google Scholar database using keywords related to hospital medical waste management in Riau. From 169 identified articles, 10 met the inclusion and exclusion criteria and were analyzed narratively. The results indicate that infectious waste and sharps are the most dominant types, mainly generated from inpatient wards, emergency departments, laboratories, and operating rooms, with an average volume of about 100–150 kg per day. Several issues were identified, including inconsistent waste segregation, substandard temporary storage facilities, limited transportation infrastructure, and high dependence on third-party services for waste treatment. In conclusion, the management of B3 solid medical waste in hospitals in Riau Province is not yet optimal and requires improved regulatory compliance, better infrastructure, and strengthened monitoring and evaluation systems.